Hybrid solvating electrolytes for practical sodium-metal batteries - Chen, Weiyin; Park, Jin Sung; Kwon, Choah; Plaza-Rivera, Christian O.; Hsu, Chia Wei; Phong, Jason Khoi; Kilgallon, Landon James; Wang, Daniel; Dai, Tao; Kim, So Yeon; Zhu, Guanzhou; Gao, Yifan; et al. (Joule, 2025)
Sodium-metal batteries could be competitive against Li-metal batteries, but their applications depend on the stability of electrolytes against sodium-metal anodes and cathodes simultaneously. Here, we propose hybrid solvating electrolytes (HSEs), composed of both strongly and weakly solvating solvents of sodium salts, to tune the solubility, solvation structure, and electrochemical decomposition properties. Fifty HSEs are prepared using the pre-screened candidate molecules, validating the mixture selection requirements and correlations between salt/solvent types and their mixture-dependent performance, including oxidative stability, Coulombic efficiency, and cycling overpotential. A model hybrid solvent formed by mixing weakly solvating N,N-dimethyltrifluoromethane sulfonamide (DMTMSA) with strongly solvating tetrahydrofuran (THF) demonstrates strong beyond-rule-of-mixture effects, showing extraordinarily stable cycling performance against Na3V2(PO4)3 and Na0.44MnO2 cathodes and Na-metal anode. Spectroscopic analysis and molecular dynamics simulations reflect the corresponding change in ion-dipole interaction and solvation structures. The strong-weak hybrid solvating principle for electrolyte design enables practical alkali-metal batteries.
Keywords: Alkali-metal battery; Donor numbers; Electrostatic potentials; Fast cycling; Fluorinated sulphonamide; Hybrid solvating electrolyte; Sodium-metal battery; Solvation structure; Strongly solvating solvent; Sulphonamides; Weakly solvating solvent; alkali-metal batteries; donor number; electrostatic potential; fast cycling; fluorinated sulfonamide; hybrid solvating electrolytes; sodium-metal batteries; solvation structure; strongly solvating solvent; weakly solvating solvent